Reported injury, hospitalization, and injury fatality rates among New Jersey adolescent workers - Uhiara, Daniel (Inj Epidemiol, 2019)
BACKGROUND: Workplace injuries are a public health concern, including among adolescents and young adults. Secondary school career-technical-vocational education related injuries are mandated by code under jurisdiction of New Jersey Department of Education to be reported online to New Jersey Safe Schools Program. These are the only U.S. law-based surveillance data for young workers in secondary school career-technical-vocational education. New Jersey Department of Health’s hospitalization and fatality records provide additional information about other secondary school career-technical-vocational education and non- secondary school career-technical-vocational education related injuries not necessarily reported to New Jersey Safe Schools Program. This report compared data available to the New Jersey Department of Health and New Jersey Safe Schools Program on injuries among young workers ages 14–21 years. METHODS: Annual work-related hospitalizations, 2007–2016, were abstracted from hospital discharge data. Denominator data from the U.S. Bureau of Labor Statistics was used to estimate annual crude rate of hospitalizations per 100,000 employed persons. Hospitalization rates were stratified by demographic data from the U.S. Bureau of Labor Statistics. Hospitalization rates for primary diagnoses and job title/status with ≥2 documented cases were reported. Annual crude fatality rates per 100,000 full time equivalent workers, age ≥ 16 years, were estimated for 1990–2016 using annual average full time equivalent workers and the U.S. National Institute Occupational Safety and Health’s Employed Labor Force Query System as denominator. RESULTS: Annual crude hospitalization rates decreased over time. Hospitalization and fatality rates were higher among young adult workers ages 19–21 years; non-Hispanic Whites; and, males. Percent fatality for ages 19–21 years was greater than ages 14–17 years and 18 years. Declines in hospitalization rates corresponded to decreases in reported injuries among career-technical-vocational education students. Age distribution varied slightly between hospital discharge data and New Jersey Safe Schools Program data. CONCLUSION: Hospitalization and fatality rates were higher among males than among females, possibly reflecting a tendency for males to engage in riskier jobs than females. Understanding injury disparities can inform public health prevention efforts. Trainings/interventions should aim at addressing the most frequently diagnosed conditions or nature of reported injuries, within those most impacted career clusters like sales/restaurant workers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40621-019-0216-9) contains supplementary material, which is available to authorized users.